2015
DOI: 10.1007/978-3-319-14977-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Geo-indistinguishability: A Principled Approach to Location Privacy

Abstract: International audienceIn this paper we report on our ongoing project aimed at protecting the privacy of the user when dealing with location-based services. The starting point of our approach is the principle of geo-indistinguishability, a formal notion of privacy that protects the user’s exact location, while allowing approximate information – typically needed to obtain a certain desired service – to be released. We then present two mechanisms for achieving geo-indistinguishability, one generic to sanitize loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
(49 reference statements)
0
22
0
Order By: Relevance
“…This method ignores the relevance of user location points and is vulnerable to a large number of inference attacks. Chatzikokolakis et al [32] showed a formal notion of privacy that protects the user's exact location-"geoindistinguishability." In [32], they proposed two mechanisms to protect the privacy of user when dealing with location-based services.…”
Section: Related Workmentioning
confidence: 99%
“…This method ignores the relevance of user location points and is vulnerable to a large number of inference attacks. Chatzikokolakis et al [32] showed a formal notion of privacy that protects the user's exact location-"geoindistinguishability." In [32], they proposed two mechanisms to protect the privacy of user when dealing with location-based services.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, their work tested the quality of the predicted location. Chatzikokolakis et al [7] also showed a formal notion of privacy that protects the user's exact location-"geo-indistinguishability". In [7], they proposed two mechanisms to protect the privacy of user when dealing with location-based services.…”
Section: Related Workmentioning
confidence: 99%
“…Chatzikokolakis et al [7] also showed a formal notion of privacy that protects the user's exact location-"geo-indistinguishability". In [7], they proposed two mechanisms to protect the privacy of user when dealing with location-based services. They extended their mechanisms to limit the degradation of the privacy guarantees due to the correlation between the points.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed system gets different speed trajectory by using a hierarchical reference method to isolate the original trajectory, and then protects the speed trajectory. Chatzikokolakis et al [32] proposed a predictive differentially-private mechanism for location privacy, which can offer substantial improvements over the independently applied noise. Their works showed that correlations in the trace can be in fact exploited in terms of a prediction function that tries to guess the new location based on the previously reported locations.…”
Section: Related Workmentioning
confidence: 99%